2019
DOI: 10.1177/1354816619887022
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting tourism’s additional impact on income

Abstract: This study revisits the question of whether tourism development is an additional determinant of income or works through other standard income determinants. Both a panel data analysis from 2006 to 2015 and a cross-sectional country average analysis reveal that the incremental effect of tourism is significantly positive, suggesting that tourism is an additional determinant of income. Further analyses show that the income effect of tourism is contingent on some country characteristics: the positive income effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…Accordingly, the study validates the TLGH for the selected countries in both the long and short run. In a similar manner, Udom Etokakpan et al ( 2019 ) confirmed the validity of the TLGH in a panel study of the world’s top four agricultural economies between 1995 and 2015, much as He and Li ( 2021 ) supported the TLGH in a panel study of selected countries between 2006 and 2015. Furthermore, while Su et al ( 2021 ) suggested that tourism drives growth in China based on time series data regressed with a VECM model, Usmani et al ( 2021 ) upheld the unidirectional causal effects from tourism to growth in BRIC countries based on a panel causality test.…”
Section: Literaturementioning
confidence: 79%
“…Accordingly, the study validates the TLGH for the selected countries in both the long and short run. In a similar manner, Udom Etokakpan et al ( 2019 ) confirmed the validity of the TLGH in a panel study of the world’s top four agricultural economies between 1995 and 2015, much as He and Li ( 2021 ) supported the TLGH in a panel study of selected countries between 2006 and 2015. Furthermore, while Su et al ( 2021 ) suggested that tourism drives growth in China based on time series data regressed with a VECM model, Usmani et al ( 2021 ) upheld the unidirectional causal effects from tourism to growth in BRIC countries based on a panel causality test.…”
Section: Literaturementioning
confidence: 79%
“…The local income level can be defined as the average economic capacity or earnings of individuals or households within a specified local area [92]. Kuznets [93] hypothesized that income inequality initially intensifies during the early stages of economic growth but begins to decrease after surpassing a certain income threshold, a phenomenon described as the Kuznets curve.…”
Section: Control Variablesmentioning
confidence: 99%